Performance investigation of differential frequency hopping - Han, Le (Nanyang Technological University, 2021)
Differential frequency hopping (DFH) is not like traditional frequency hopping (FH) because the frequency transfer function (FTF) is combined with sending information. The current hop frequency is not only decided on past hopping frequency, but also the current input is related to it. Though the consideration of FTF makes it more complex, the hopping rate is faster than that of an FH system, thereby having better anti-jamming ability compared with a conventional FH system. To investigate the performance of the DFH system, the basic knowledge of the FH system is necessary and binary frequency-shift-keying (BFSK) modulation is also important to understand the DFH system. In addition, convolutional coding and the Viterbi algorithm are core technologies for DFH systems. The process of coding and its trellis diagram will be discussed in this report. Moreover, the comparison of bit error rate (BER) simulations of FH systems and DFH systems is discussed in this report. Besides simulations in additive white Gaussian noise (AWGN) channels, partial-band noise jamming (PBNJ) is also included in the simulations. Finally, the impact of different convolutional encoders and the number of frequencies in DFH is simulated in the report. Keywords: Differential frequency hopping, frequency transfer function, convolutional coding, partial-band noise jamming.